2002
DOI: 10.1002/app.10095
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated polyester as compatibilizer for styrene–butadiene (SBR)/acrylonitrile–butadiene (NBR) rubber blends

Abstract: ABSTRACT:The effect of the addition of 5 and 10 phr of unsaturated polyester resin (UPE) on the compatibility and physicomechanical properties of styrene-butadiene (SBR) and acrylonitrile-butadiene (NBR) rubber blends was studied. Differential scanning calorimetry (DSC), scanning electron microscopy (SEM), electrical, and ultrasonic techniques were used to determine the degree of the compatibility (DC). The results obtained revealed that, by the addition of 10 parts per hundred parts of rubber (phr) UPE as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…7 The effect of unsaturated polyester (UPE) on the compatibility of SBR/NBR in their physical blends was studied with ultrasonic velocity and attenuation measurements. 8 The effect of some compatibilizers on the compatibility of SBR/NBR rubber blends has been studied. The investigated compatibilizers were a) a polymeric compatibilizer, namely, acrylonitrile-butadiene-styrene (ABS); b) low molecular weight compounds, such as divinylbenzene (DVB) and triethylene glycol dimethylacrylate (TEGDMA); and c) graft copolymers, such as SBR-g-AN, NBR-g-St, BR-g-AN, and BR-g-St.…”
Section: Introductionmentioning
confidence: 99%
“…7 The effect of unsaturated polyester (UPE) on the compatibility of SBR/NBR in their physical blends was studied with ultrasonic velocity and attenuation measurements. 8 The effect of some compatibilizers on the compatibility of SBR/NBR rubber blends has been studied. The investigated compatibilizers were a) a polymeric compatibilizer, namely, acrylonitrile-butadiene-styrene (ABS); b) low molecular weight compounds, such as divinylbenzene (DVB) and triethylene glycol dimethylacrylate (TEGDMA); and c) graft copolymers, such as SBR-g-AN, NBR-g-St, BR-g-AN, and BR-g-St.…”
Section: Introductionmentioning
confidence: 99%
“…SBR/NBR blend is considered as a compatible blend due to the fact that the styrene in SBR and the nitrile groups in NBR could form a donor-acceptor system which produces ease compatibility. Mansour et al [10] , have investigated the effect of unsaturated polyester as compatibilizer on SBR/NBR blends, while Ramesan et al found that Blends of SBR and NBR are to be immiscible and its compatibility can be achieved by using dichlorocarbene modified (DCSBR) as a compatibilizer. In addition, the effect of DCSBR on cure characteristics, swelling behaviour, mechanical properties, oil resistance and air ageing behaviour is also studied [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic and natural rubbers and elastomers in solid and liquid forms have been applied to improve UPE damping properties. Rubbers such as natural rubber latex (NRL) [16,18] and styrene-butadiene rubber (SBR) latex [19,20], and functional elastomers such as hydroxyl-terminated polybutadiene, deoxidized natural rubber, hydroxyl terminated natural rubber, and maleated nitrile rubber [15] have been used to enhance UPE damping properties. Also Polyoxypropylenetriamine (POPTA) has also been employed, combined with temperature during curing, to optimize the damping factor and mechanical properties of UPE [21].…”
Section: Introductionmentioning
confidence: 99%